Mechanical Alterations Associated with Repeated Treadmill Sprinting under Heat Stress. - Olivier Girard; Franck Brocherie; Jean-Benoit Morin; Sébastien Racinais; Grégoire P Millet; Julien D Périard (PLoS ONE, 2017)
Purpose Examine the mechanical alterations associated with repeated treadmill sprinting performed in HOT (38°C) and CON (25°C) conditions. Methods Eleven recreationally active males performed a 30-min warm-up followed by three sets of five 5-s sprints with 25-s recovery and 3-min between sets in each environment. Constant-velocity running for 1-min at 10 and 20 km.h-1 was also performed prior to and following sprinting. Results Mean skin (37.2±0.7 vs. 32.7±0.8°C; P<0.001) and core (38.9±0.2 vs. 38.8±0.3°C; P<0.05) temperatures, together with thermal comfort (P<0.001) were higher following repeated sprinting in HOT vs. CON. Step frequency and vertical stiffness were lower (-2.6±1.6% and -5.5±5.5%; both P<0.001) and contact time (+3.2±2.4%; P<0.01) higher in HOT for the mean of sets 1-3 compared to CON. Running distance per sprint decreased from set 1 to 3 (-7.0±6.4%; P<0.001), with a tendency for shorter distance covered in HOT vs. CON (-2.7±3.4%; P = 0.06). Mean vertical (-2.6±5.5%; P<0.01), horizontal (-9.1±4.4%; P<0.001) and resultant ground reaction forces (-3.0±2.8%; P<0.01) along with vertical stiffness (-12.9±2.3%; P<0.001) and leg stiffness (-8.4±2.7%; P<0.01) decreased from set 1 to 3, independently of conditions. Propulsive power decreased from set 1 to 3 (-16.9±2.4%; P<0.001), with lower propulsive power values in set 2 (-6.6%; P<0.05) in HOT vs. CON. No changes in constant-velocity running patterns occurred between conditions, or from pre-to-post repeated-sprint exercise. Conclusions Thermal strain alters step frequency and vertical stiffness during repeated sprinting; however without exacerbating mechanical alterations. The absence of changes in constant-velocity running patterns suggests a strong link between fatigue-induced velocity decrements during sprinting and mechanical alterations.